Intradiscal Injection of a Slow Release Formulation of Celecoxib for the Treatment of Dogs with Low Back Pain. Issue 1 (April 2016) - Tellegen, Anna; Beukers, Martijn; Miranda-Bedate, Alberto; Willems, Nicole; De Leeuw, Mike; Van Dijk, Maarten; Creemers, Laura; Tryfonidou, Marianna; Meij, Björn
Introduction: Intervertebral disc (IVD) disease characterized by low back pain is common in both humans and large breed dogs. Inflammatory mediators such as prostaglandin E2 (PGE2) play a key role in IVD degeneration, causing structural changes of the IVD and low back pain. The current conservative and surgical treatment modalities do not reverse IVD degeneration and have certain drawbacks. Long term systemic administration of non-steroidal anti-inflammatory drugs can cause gastro-intestinal side effects. Decompressive surgery is effective in over 80% of the patients, but is rather costly and has a long recovery period. Injectable formulations that enable local sustained release of anti-inflammatory drugs aim at decreasing inflammation and thereby inhibiting degeneration and pain. In vitro, controlled release of celecoxib, a COX-2 inhibitor, from a thermoreversible acetyl-capped PCLA-PEG-PCLA hydrogel inhibited PGE2 production and enhanced matrix production for 28 days in 3D culture of canine nucleus pulposus cells that were subjected to the catabolic effects of TNF-α. In vivo, sustained release of celecoxib by the hydrogel for up to 60 days was shown and safely applied intradiscally in laboratory dogs with naturally occurring IVD degeneration. The aim of the present study is to report the safety and feasibility of intradiscal application in client-owned dogs with low back pain related to IVD degeneration. Material and Methods: Client-owned dogs with low back pain were diagnosed by MRI with degenerative lumbosacral stenosis marked by mild to moderate IVD degeneration and protrusion. The dogs were surgical candidates but were offered intradiscal injection. The PCLA-PEG-PCLA thermogel, loaded with 0.013mg/ml celecoxib, was percutaneously injected into the nucleus pulposus of L7-S1 under fluoroscopy guidance. Follow-up consisted of clinical examination, owner questionnaires, and objective gait analysis by measurement of ground reaction forces (GRFs) using force plate analysis (FPA) at 6 weeks, and 3 and 6 months after injection. MRI was repeated after 3 months and included T2- and T1-weighted images and T2-mapping. Results: Ten dogs with DLLS were injected with the celecoxib-loaded hydrogel. None of the dogs showed adverse reactions after intradiscal injection. Follow up MRI showed no worsening of the IVD degeneration. Clinical improvement was achieved by reduction of low back pain in 9/10 dogs, as was shown by clinical examination, force plate analysis and owner questionnaires. In 3/10 dogs low back pain recurred at 3 months and they subsequently underwent standard-of-care surgical treatment. Conclusion: This study showed the safety and feasibility of intradiscal injections with a thermoresponsive hydrogel loaded with celecoxib. Ongoing studies concentrate on the long term clinical follow up of these patients. Future studies will determine the optimal loading dose of celecoxib for clinical efficacy. In this setup, the dog can be used as a model for the development of novel treatment modalities in both canine and human patients with chronic low back pain.